Breast tissue mimicking phantoms for combined ultrasound and microwave imaging. (13th December 2021) - Li, Siyun; Fear, Elise; Curiel, Laura
Abstract: We present a new formulation for a breast tissue-mimicking phantom for combined microwave and ultrasound imaging to assist breast cancer detection. Formulations based on coconut oil, canola oil, agar and glass beads were used to mimic skin and fat tissues. First, 36 recipes were fabricated, and properties were measured to determine the relationship and possible interaction between ingredients with the ultrasound and microwave properties. Based on these results, the formulae were developed to mimic different tissues found in breast, including skin, fat, fibroglandular, and tumour tissues. All phantoms contained a base of agar and glass beads at different proportions depending on the tissue mimicked. Tumour and fibroglandular tissues were best mimicked by adding polyvinylpyrrolidone (PVP), while using coconut oil for skin and canola oil for fat produced the best results. Five final phantoms with different internal structures were fabricated and imaged using B-mode ultrasound and a microwave transmission system. Microwave permittivity maps were obtained from the microwave system and compared to ultrasound images. The structure and composition of the phantoms were all confirmed through this microwave and ultrasound imaging.